Penerapan Perkembangan Kognitif Jean Piaget dan Perkembangan Bahasa Vygotsky dalam Pembelajaran - Habsy, Bakhrudin All; Rachmawati, Amalia Putri; Wiyono, Rima Faradillah Wati Fidaus; Rakhmanita, Aulia (Lembaga Yasin AlSys, 2024)
In this research, researchers are interested in examining the application of Jean Piaget's cognitive development and Vygotsky's language development in learning. The aim of this research is to deepen understanding of the application of Jean Piaget's cognitive theory and Vygotsky's language theory in learning. In his research, the researcher used a qualitative approach through literature study. Literature study is the object studied in this research, namely the application of Jean Piaget's cognitive development and Vygotsky's language development. The results of this research can be said that language development is closely related to cognitive development.